A NEW SOLUTION ALGORITM FOR THE TRANSPORTATION MODEL - Sait Patır (Sosyal Ekonomik Araştırmalar Dergisi)
In this article, we have theoretically tried to solve the transportation model with a new algorithm and compare it with the existing solution methods. The solution aim of the transportation model is to meet the total demand and total supply in order to minimize the total cost. For this purpose, the problem can be solved by three methods. These methods are: North-West Diagonal method, Least Cost Method and Vogel’s method. The order of these methods in terms of giving the most optimal initial solutions is Vogel approach, Least Cost and North-West Diagonal. With this new algorithm and proposed two rules; the solution of the problem is much more optimal than the existing ones in case of the same values in the same column or rows and alternative ones. For this purpose, two model problems were first solved by the new method and then by Least Cost and Vogel method (without North-West Diagonal method); and then the results were compared. It was found out that the new algorithm gave the most optimal and the most suitable initial solutions. When we are applying Rule1 and Rule2 with Vogel method we get better result. It means that, we get nearer optimal solution than normal Vogel method. This method gives better result then other used methods. We can propose as an alternative.